Enhancing salt tolerance in rice genotypes through exogenous melatonin application by modulating growth patterns and antistress agents - Mohammad Ubaidillah; Muhammad Farooq; Kyung-Min Kim (Scientific Reports)
Abstract Melatonin is a bioactive molecule with an important role in plants responding to various abiotic and biotic stresses. This study aims to determine the role of melatonin in rice under salt stress. This study used a factorial completely randomized design. The first factor was local rice varieties (IR64 and Silaun), and the second factor was plant treatments (control, 1 µM melatonin, 150 mM NaCl, 150 mM NaCl + 1µM melatonin). This study shows that exogenous melatonin can increase plant growth, such as plant height, root length, stem length, leaf length, leaf area, and plant biomass under salt stress compared to treatment without melatonin. Exogenous melatonin can increase the total chlorophyll content, relative water content, and proline content, reduce the total sodium content, and increase potassium absorption under conditions of salinity stress. Melatonin is also able to scavenge ROS in plants, resulted the decrease in ROS and MDA content. In terms of gene expression, OsAPX1 and cytosolic APX exhibited the highest expression in IR64 under combined salt and melatonin treatment, while GPOD, Mn-SOD, and Cu/Zn-SOD were upregulated under various conditions in both varieties. Additionally, OsLEA showed high expression in both varieties under control conditions, and CAT was significantly upregulated under salt stress. Our findings indicate that exogenous melatonin has the potential to enhance various factors under salt stress and helping in the recovery of rice plants from sodium (Na+) damage.